Cities of Rus’ in the military operations of the Piasts against the Rurikids (11 – mid- of the 14 centuries). Part 2 - Voloshchuk, Myroslav (City and War, 2021)
The article is devoted to the analysis of the military campaigns of the Piasts into the lands of the Rurikids with further siege, assault and the capture of the Ruthenian towns or entry into them without any resistance. In general considering very active interdynasty dialogue in all possible planes, at the same time we emphasize the high intensity of the invasions of the Poles into the neighboring eastern lands. The total number of the campaigns that ended during the 11th–14th centuries with the devastation of the towns of the Rurikids or their environs was at least 24. In addition, the Poles more than 10 times entered in Rus’, appearing in certain cities as a defenders, an allies, a guardians, a protectors of the local Ruthenian princes, especially during the first decades of the 13th c entury. A mong t he m ost d ramatic i n t he a ftermath o f the looting were the entry of Boleslav the Brave into Kyiv in 1018, the capture of Volhynian Volodymyr by Leszek the White in 1207/8, and also by Leszek the Black in 1280 – Lviv and Perevoresk. The example of the capture of Lviv by Casimir III in 1340 – should be consider separately. At the same time, with the exception of the description of the siege in August 1245 by Yaroslav, we do not have any other evidence of the engineering thought, tactics and strategy of the preparing for an assaults and the capture of Rus’ian fortifications by the Piast. It is quite possible that the sources simply did not attach much importance to this.